A placebo‐controlled proof‐of‐concept study of alirocumab on postprandial lipids and vascular elasticity in insulin‐treated patients with type 2 diabetes mellitus. Issue 5 (27th January 2020) - Burggraaf, Benjamin; Pouw, Nadine M.C.; Arroyo, Salvador Fernández; van Vark‐van der Zee, Leonie C.; van de Geijn, Gert‐Jan M.; Birnie, Erwin; Huisbrink, Jeannine; van der Zwan, Ellen M.; Mulder, Monique T.; Rensen, Patrick C.N.; de Herder, Wouter W.; Cabezas, Manuel Castro
Abstract: Aim: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of cardiovascular disease (CVD) linked to atherogenic dyslipidaemia and postprandial hyperlipidaemia. Alirocumab, a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, improves CVD risk by reducing the concentration of low‐density lipoprotein‐cholesterol (LDL‐C). However, effects of PCK9 inhibitors on other aspects of diabetic dyslipidaemia, particularly in the postprandial situation, are less clear. Material and Methods: Twelve male patients with T2DM on an intensive insulin regimen completed a 6‐week randomized, double‐blind, placebo‐controlled, proof‐of‐concept study. Participants received three biweekly dosages of subcutaneous alirocumab (150 mg) or placebo. Before and after the intervention, fasting and postprandial triglyceride (TG) plasma levels, apolipoprotein (apo) B48, lipoprotein composition isolated by ultracentrifugation, vascular function and markers of inflammation were evaluated. Results: Alirocumab treatment reduced fasting plasma TG levels (between group median change −24.7%; P = 0.018) and fasting apoB48 serum levels (−35.9%; P = 0.039) compared with placebo. Alirocumab reduced the plasma TG area under the curve (AUC) (−26.4%; P = 0.006) and apoB48 AUC (−55.7%; P = 0.046), as well as plasma TG incremental AUC (−21.4%; P = 0.04) and apoB48 incremental AUC (−26.8%; P = 0.02). In addition, alirocumab reduced fasting and postprandial TG levels in very low‐density lipoprotein (VLDL) and LDL. Alirocumab improved fasting pulse wave velocity, but no changes in postprandial markers of inflammation were observed. Conclusions: In addition to the well‐known LDL‐C‐reducing effects, 6 weeks of alirocumab treatment lowered both fasting and postprandial plasma TG levels by reducing the TG levels in VLDL and LDL and the concentration of intestinal remnants.